Corneal Ulcers in a Cat - Treatment with n-butyl-2-cyanoacrylate Adhesive - Pigatto, João Antônio Tadeu; Méndez, Natália Pons; Siebel, Maiara Poersch; Cargnin, Luísa Soares; da Silva, Alessandra Fernandez; Rocha, Rafaella Silva; de Melo, Alana Pinto; Martins, Marina Assunção (Acta Scientiae Veterinariae, 2024)
Background: When left untreated, corneal ulcers can progress unfavorably, posing a risk to the vision of an animal. The application of cyanoacrylate adhesive offers an alternative for treating deep ulcers without the need for surgical intervention that requires using sutures on the cornea. This adhesive not only has antibacterial properties but also demonstrates antifungal efficacy. Moreover, it is easily accessible and cost-effective, making it a promising solution. The objective is to report a case of deep corneal ulcers in a cat successfully treated with n-butyl-2-cyanoacrylate adhesive. Case: A 4-month-old male Persian cat had been experiencing ocular discomfort and tearing for 7 days. There was no reported history of previous ocular trauma, and no treatment had been administered. Examination of the right eye revealed severe blepharospasm, photophobia, epiphora, conjunctival hyperaemia, chemosis, miosis and mucopurulent ocular discharge. Pupillary light reflexes, including direct, consensual and dazzle reflexes, were tested with a light source and were within normal limits, with preserved vision. No abnormalities were observed in the left eye. Using a portable slit lamp, 5 deep stromal corneal ulcers were observed in the right eye, along with mild diffuse corneal edema. Fluorescein staining was performed, and the dye impregnated all corneal ulcers. All ulcers were less than 3 mm in diameter. During the same consultation, the application of n-butyl-2-cyanoacrylate adhesive (Hystoacryl®) at the lesion sites and covering with the third eyelid were indicated. The epithelium near the lesions was debrided with a scalpel blade, and the lesion sites were dried with cellulose sponges before applying cyanoacrylate adhesive using an insulin syringe and needle. All corneal ulcers were covered with the adhesive. After 1 min, the adhesive was polymerised using Ringer’s lactate solution applied with a 3 mL syringe. Tobramycin 0.3% eye drops [every 4 h for 15 days] and sodium flurbiprofen-based eye drops [every 4 h for 15 days] were prescribed. In addition, 1% atropine sulphate ophthalmic ointment was prescribed [SID for 5 days]. To prevent self-trauma, the use of an Elizabethan collar was recommended for 15 days. Weekly evaluations were conducted. Twenty-one days after the procedure, intense corneal opacity and granulation tissue were observed at the lesion sites. The fluorescein staining test was negative. Thirty days after the procedure, remission of granulation tissue and decreased corneal neovascularization were observed, and finally, after 6 months, only mild opacity was present in the area where the adhesive had been applied, and the remaining cornea stayed transparent. The patient had visual function. Discussion: The advantages of cyanoacrylate adhesives include short surgical time, bacteriostatic activity against gram-positive bacteria, inhibition of inflammatory cell migration and collagenase formation, low cost, easy and rapid polymerization and the absence of the need for sutures. Despite the widespread use of cyanoacrylate adhesive in human ophthalmology, its application in animals is still limited, with few documented and reported clinical cases. Compared to other methods employed for the surgical treatment of corneal ulcers, cyanoacrylate adhesive offers several advantages, such as easy and quick application and not requiring sutures in the cornea. In this case, all the ulcers were up to 3 mm in diameter each, and the treatment of them was successful. Besides maintaining the integrity of the eyeball, the adhesive served as a support for healing. The patient maintained visual function with a transparent cornea. Keywords: cat, ophthalmology, cyanoacrylate adhesive.